2020
DOI: 10.1016/j.euf.2019.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and Harms of Electrical Neuromodulation for Chronic Pelvic Pain: A Systematic Review

Abstract: Chronic pelvic pain (CPP) is chronic or persistent pain perceived in structures related to the pelvis of men and women. These individuals may suffer significant distress and detriment to their daily living and quality of life. Neuromodulation may provide an effective treatment option in patients with CPP refractory to standard treatment, reducing pain and improving quality of life with an acceptable rate of complications. However, study quality is insufficient for a more certain conclusion, and therefore large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 48 publications
(52 reference statements)
4
26
0
Order By: Relevance
“…The most robust systematic review for chronic pelvic pain was published by Cottrell et al [ 71 ] in 2020 and concluded that TENS was beneficial for women with chronic pelvic pain secondary to dysmenorrhea. Cottrell et al [ 71 ] reported the overall effect size for data extracted for various neuromodulation treatments including percutaneous tibial nerve stimulation and transcutaneous interferential electrical stimulation that included 2 RCTs on TENS (87 participants), but did not report the effect size for TENS per se. Cottrell et al, conducted a separate analysis that pooled data from various neuromodulation techniques that included 4 non-RCTs on TENS (131 participants), but did not report the effect estimate for TENS per se.…”
Section: Resultsmentioning
confidence: 99%
“…The most robust systematic review for chronic pelvic pain was published by Cottrell et al [ 71 ] in 2020 and concluded that TENS was beneficial for women with chronic pelvic pain secondary to dysmenorrhea. Cottrell et al [ 71 ] reported the overall effect size for data extracted for various neuromodulation treatments including percutaneous tibial nerve stimulation and transcutaneous interferential electrical stimulation that included 2 RCTs on TENS (87 participants), but did not report the effect size for TENS per se. Cottrell et al, conducted a separate analysis that pooled data from various neuromodulation techniques that included 4 non-RCTs on TENS (131 participants), but did not report the effect estimate for TENS per se.…”
Section: Resultsmentioning
confidence: 99%
“…They are the most effective treatments for CPP despite possible complications also being reported. [ 1 3 4 ]…”
Section: Discussionmentioning
confidence: 99%
“…Engineering advances focus on increasing SCS efficacy[ 1 2 3 4 ] by stimulating the correct target (with anatomically guided 3D neural targeting), [5] and the surge of new devices.…”
Section: Introductionmentioning
confidence: 99%
“…PNS for pelvic pain has been the subject of systematic reviews in the gynecologic literature [ 41 , 42 ] and is included here, as interventional pain physicians regularly treat pelvic pain. Shah et al also described the numerous techniques of PNS for chronic pelvic pain, particularly pudendal neuralgia [ 43 ].…”
Section: Methodsmentioning
confidence: 99%